Composition simultaneously containing mussel mucin and anionic polysaccharide substance as well as preparation method and product thereof
By adding inorganic salt or citric acid to the aqueous solution of mussel mucin and anionic polysaccharide substances, the problem of complex compatibility between the two is solved, and long-term stability and efficiency improvement are achieved.
Patent Information
- Application Number
- CN202411477217.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-22
Smart Images

Figure CN119454492A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of raw materials, and in particular to a composition containing mussel mucin and anionic polysaccharide substances, and a preparation method and product thereof. Background Art
[0002] Mussel mucin is a substance secreted by mussels to fix themselves on reefs, the bottom of ships and other surfaces. Due to its strong wet adhesive ability, it has attracted the attention of scientists. As scientists studied it, they found that the substance that can allow mussels to fix on the surface of wet objects for a long time is a type of protein, and it was named "mussel mucin". With continuous research, from the discovery and naming of this type of substance in 1980, to 1982, Professor Bent Samuelsson discovered that it has a strong anti-inflammatory function. Subsequently, many companies around the world have studied the application of this substance. Since this substance was extracted from organisms such as mussels in the early days, its production is extremely rare and is called soft gold of the ocean. However, with the advancement of science and technology, with the help of synthetic biology technology, its product output can be greatly increased, so that it can cover more application fields, not limited to the research and application of wet adhesives.
[0003] There are many types of anionic polysaccharides, with a wide range of sources and many application fields, such as skin feel regulators or active ingredients. In the product application field, for example, the extracellular polysaccharide xanthan gum derived from the fermentation of Xanthomonas campestris has unique rheological properties, good water solubility, heat and acid-base stability, and good compatibility with a variety of salts. As a thickener, suspending agent, emulsifier, and stabilizer, it can be widely used in more than 20 industries such as food, petroleum, and medicine. It is currently the world's largest-scale and widely used microbial polysaccharide. Sclerotium gum, also known as sclerotium polysaccharide, is a new type of non-ionic biopolysaccharide polymer decomposed by the fungus plant Sclerotium sclerotiorum. It has many excellent properties, such as high viscosity, high stability, moisturizing, anti-inflammatory, antioxidant, thickening, skin improvement, good hydrolysis, etc. It is widely used in cosmetics, medicine, papermaking, food, packaging and other fields. Another type of high-molecular polysaccharides derived from fermentation, such as hyaluronic acid or its salts, polyglutamic acid or its salts, etc., not only have the effect of regulating viscosity, but more importantly, they have excellent skin moisture-locking effect. Polysaccharides derived from plants, such as β-glucan, tremella polysaccharide, and dendrobium polysaccharide, all have excellent moisturizing and repairing effects.
[0004] Specially, for hyaluronic acid or its salt, it has high clinical value and wide application.Hyaluronic acid or its salt is widely present in many parts of human body, such as extracellular matrix (ECM), eyes, joints etc. of skin, plays a very big role, has high clinical value.Hyaluronic acid or its salt is widely used in various ophthalmic surgeries, such as lens implantation, corneal transplantation and anti-glaucoma surgery etc.It can also be used to treat arthritis and accelerate wound healing.It is used in cosmetics, can play a unique role in protecting skin, can keep skin moisturized smooth, delicate and tender, elastic, has anti-wrinkle, anti-wrinkle, beauty care and the effect of recovering skin physiological function.
[0005] With the development of modern medicine, more and more research results show that the deficiency of trace elements and vitamins is associated with the occurrence of skin diseases. Some chemical elements exist in very small quantities in the human body, but have certain physiological functions and must be taken in through food. They are called essential trace elements. The physiological functions of trace elements are mainly: (1) essential active factors for enzymes and vitamins; (2) constituting certain hormones or participating in the action of hormones; (3) participating in nucleic acid metabolism; (4) assisting constant elements and macronutrients to play their roles. For example, zinc is an essential trace element for the human body. It participates in the synthesis of many enzymes in the body and the metabolism of proteins, sugars, and fats. It affects protein synthesis and wound healing, and can maintain the elasticity, toughness, density, tenderness and smoothness of the skin and mucous membranes. Copper is a component of more than 30 enzymes in the human body, participates in redox and tissue respiration, and promotes the absorption and utilization of iron. It is also of certain significance to maintain the physiological function of the skin. Blue copper peptide is based on tripeptide-1 and chelates copper ions, thereby playing many skin care effects such as anti-inflammatory, repair, and firming. Other trace elements such as potassium, sodium, iron, magnesium, selenium, etc., all play an important role in the human body.
[0006] Mussel mucin is a naturally positively charged protein with a molecular weight of about 14-100kDa. In addition to its powerful anti-inflammatory function, it also has outstanding effects in skin repair, inflammatory pigmentation, free radicals, film formation, etc. Anionic polysaccharides are naturally negatively charged and have a wide range of applications.
[0007] The above two substances are both substances with excellent functions, whether in the medical field or in the field of daily chemical and medical beauty, and their application ranges match each other and their functions complement each other. A large number of product developers and consumers hope to add the two active ingredients to a product at the same time for joint use, expecting safer and more effective results and meeting expectations for a better life. However, given the natural structural properties of the two, it is difficult to compound the two together in application. Forcibly compounding the two will produce a neutralization reaction in the chemical reaction. Since their respective molecular weights are relatively large, the appearance will show flocculation and precipitation, which not only affects the appearance, but also causes the original efficacy to be inactivated.
[0008] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0009] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a composition containing both mussel mucin and anionic polysaccharides, and a preparation method and product thereof, aiming to solve the problem of the existing composite compatibility of mussel mucin and anionic polysaccharides.
[0010] The technical solution of the present invention is as follows:
[0011] The first aspect of the present invention provides a composition containing both mussel mucin and anionic polysaccharide substances, wherein, by mass, the composition includes 0.01-0.2 parts of mussel mucin, 0.05-1.0 parts of anionic polysaccharide substances, 0.3-3.0 parts of inorganic salts or citric acid, and 75.0-95.0 parts of water.
[0012] Optionally, the composition specifically includes, by mass, 0.01-0.2 parts of mussel mucin, 0.05-1.0 parts of anionic polysaccharides, 0.3-3.0 parts of inorganic salts or citric acid, 3.0-20.0 parts of small molecule sugars and 75.0-95.0 parts of water, wherein the number of sugar units in the small molecule sugars is less than 10.
[0013] Optionally, the composition specifically includes, by mass percentage, 0.01-0.2% mussel mucin, 0.05-1.0% anionic polysaccharide, 0.3-3.0% inorganic salt or citric acid, 3.0-20.0% small molecule sugar, 1.0-3.0% preservative, 2.0-20.0% polyol and water to 100%, wherein the number of sugar units of the small molecule sugar is less than 10.
[0014] Optionally, the small molecule sugar substance is selected from at least one of mannitol, trehalose, sorbitol, xylitol, raffinose and sucrose.
[0015] Optionally, the inorganic salt is selected from at least one of potassium salt, sodium salt, calcium salt, zinc salt, copper salt and magnesium salt.
[0016] Optionally, the inorganic salt is selected from at least one of potassium chloride, sodium chloride, calcium chloride, zinc chloride, zinc sulfate, copper sulfate and magnesium sulfate.
[0017] Optionally, the anionic polysaccharide substance is selected from at least one of hyaluronic acid or its salt, polyglutamic acid or its salt, colanic acid or its salt, and β-glucan.
[0018] Optionally, the molecular weight of the hyaluronic acid or its salt is 0.1-2500 KDa.
[0019] Further optionally, the molecular weight of the hyaluronic acid or its salt is 0.3-1800 KDa.
[0020] The second aspect of the present invention provides a method for preparing the composition containing both mussel mucin and anionic polysaccharide substances as described in the present invention, which comprises the steps of mixing mussel mucin, anionic polysaccharide substances, inorganic salts or citric acid and water to obtain the composition.
[0021] Optionally, the step of mixing mussel mucin, anionic polysaccharide substance, inorganic salt or citric acid and water specifically comprises: adding inorganic salt or citric acid to the aqueous solution of anionic polysaccharide substance, and then adding mussel mucin.
[0022] The third aspect of the present invention provides a product, wherein the product comprises the composition of the present invention containing both mussel mucin and anionic polysaccharide substances.
[0023] Optionally, the product is a skin care product.
[0024] Further optionally, the skin care product includes one of a facial mask, a medical dressing, a facial cream, a lotion, a freeze-dried powder, an essence, and a toner.
[0025] Beneficial effects: The present invention can form a uniform and transparent composition by adding inorganic salts or citric acid to an aqueous solution containing mussel mucin and anionic polysaccharide substances. This strategy can make the mussel mucin and anionic polysaccharide substances compatible and compounded, and have long-term stability, and can withstand the aging experimental test of the product shelf life, greatly improving the application scope and application efficacy of the above two substances. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a graph showing the compatibility test results of different compositions of Example 1.
[0027] Figure 2 The long-term stability pictures of different compositions containing potassium chloride and polysaccharides of Example 1 are shown.
[0028] Figure 3 This is a graph showing the compatibility test results of different compositions when the sodium hyaluronate in Example 2 is high molecular weight sodium hyaluronate.
[0029] Figure 4 This is a graph showing the compatibility test results of different compositions when the sodium hyaluronate in Example 2 is medium molecular weight sodium hyaluronate.
[0030] Figure 5 This is a graph showing the compatibility test results of different compositions when the sodium hyaluronate in Example 2 is low molecular weight sodium hyaluronate.
[0031] Figure 6 The long-term stability graph of different sodium chloride-containing compositions of Example 2 is shown in FIG.
[0032] Figure 7 This is a graph showing the compatibility test results of different compositions of Example 3.
[0033] Figure 8 The long-term stability pictures of different compositions containing calcium chloride of Example 3 are shown.
[0034] Fig. 9 This is a graph showing the compatibility test results of different compositions containing copper sulfate in Example 4.
[0035] Fig.10 This is a graph showing the compatibility test results of different compositions containing tripeptide-1 copper in Example 4.
[0036] Fig.11 The long-term stability pictures of different compositions of Example 4 are shown in FIG.
[0037] Fig.12 This is a graph showing the compatibility test results of different compositions containing zinc sulfate in Example 5.
[0038] Fig.13 This is a graph showing the compatibility test results of different compositions containing zinc chloride in Example 5.
[0039] Fig.14 The long-term stability pictures of different compositions of Example 5 are shown in FIG.
[0040] Fig.15 This is a graph showing the compatibility test results of different compositions containing citric acid in Example 6.
[0041] Fig.16 This is a graph showing the compatibility test results of different malic acid-containing compositions of Example 6.
[0042] Fig.17 The figure is a compatibility test result diagram of different compositions containing glycolic acid in Example 6.
[0043] Fig.18 This is a graph showing the compatibility test results of different compositions containing lactic acid in Example 6.
[0044] Fig.19 The long-term stability pictures of different compositions containing citric acid of Example 6 are shown in FIG.
[0045] Fig. 20 The graph showing the changes in moisture content of the stratum corneum of the skin tested for different samples in Example 7.
[0046] Fig.21 The graph showing the changes in transepidermal water loss rate of the skin for different samples tested in Example 7.
[0047] Fig. 22 This is a graph showing the changes in the skin a value of different samples tested in Example 7.
[0048] Fig.23 The skin erythema index change graph for different samples tested in Example 7.
[0049] Fig.24 The skin redness improvement change graphs for the different samples of Example 7 were tested.
[0050] Fig.25 This is a graph showing the change in the number of under-eye wrinkles tested on different samples in Example 7.
[0051] Fig.26 This is a graph showing the length changes of under-eye wrinkles tested for different samples in Example 7.
[0052] Fig. 27 This is a graph showing the change in the number of crow's feet when testing different samples in Example 7.
[0053] Fig.28 This is a graph showing the change in length of caudal wrinkles tested for different samples in Example 7.
[0054] Fig.29 This is a graph showing the changes in firming and anti-wrinkle efficacy of different samples in Example 7.
[0055] Fig.30 This is a diagram of the eczema repair changes in Example 7.
[0056] Fig.31 This is a diagram showing the changes in burn repair in Example 7.
[0057] Fig.32 This is a graph showing the compatibility test results of different compositions of Example 8. DETAILED DESCRIPTION
[0058] The present invention provides a composition containing mussel mucin and anionic polysaccharide substances, and a preparation method and product thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0059] Due to the natural structural properties of mussel mucin and anionic polysaccharides, it is difficult to use them together. Forcibly mixing the two together will produce a neutralization reaction in the chemical reaction. Since their molecular weights are relatively large, the appearance will appear flocculated and precipitated, which not only affects the appearance, but also causes the original efficacy to be inactivated.
[0060] At present, in order to solve the problem of the compatibility of mussel mucin and anionic polysaccharide substances, the commonly used method is to hydrolyze mussel mucin to produce amino acid fragments, thereby reducing its positive charge strength. In addition, because small fragments are formed, the molecular weight is reduced. Even if a neutralization reaction occurs, it is difficult to observe the change because the molecular weight is very small (a few amino acids). However, the structure of a substance determines the properties of the substance, so hydrolyzing the above two active ingredients is a compounding strategy, but it also loses the original function of the substance to a certain extent.
[0061] Therefore, in order to solve the compatibility problem of mussel mucin and anionic polysaccharide substances, and give full play to the advantages of the combined application of mussel mucin and anionic polysaccharide substances, the study found that by adding an appropriate amount of inorganic salt to an aqueous solution of a certain content of mussel mucin and anionic polysaccharide substances (such as hyaluronic acid or its salt), a uniform and transparent composition can be formed.
[0062] Specifically, an embodiment of the present invention provides a composition containing both mussel mucin and anionic polysaccharide substances, wherein, by mass, the composition includes 0.01-0.2 parts of mussel mucin, 0.05-1.0 parts of anionic polysaccharide substances, 0.3-3.0 parts of inorganic salts or citric acid, and 75.0-95.0 parts of water.
[0063] The embodiment of the present invention forms a uniform and transparent composition by adding an appropriate amount of inorganic salt or citric acid to an aqueous solution containing mussel mucin and anionic polysaccharide substances (such as hyaluronic acid or its salt). This compounding strategy allows the mussel mucin and anionic polysaccharide substances to be compatible and compounded, and has long-term stability, and can withstand aging experimental inspection and testing during the shelf life of the product, greatly improving the application scope and application efficacy of the above two substances.
[0064] The embodiment of the present invention allows the two active substances to be compounded and compatible without losing the structure of mussel mucin and the structure of anionic polysaccharide substances, and ensures long-term stability. It solves the compatibility problem of the combined use of the two active substances, promotes a wider application range of the composition, synergistically improves the efficacy of use, and generates greater economic benefits.
[0065] The embodiment of the present invention can form a uniform and transparent composition by adding an appropriate amount of inorganic salt to an aqueous solution containing mussel mucin and anionic polysaccharide substances. This may be because after adding an appropriate amount of inorganic salt to an aqueous solution of anionic polysaccharide substances, the metal cations of the inorganic salt will gather in the negatively charged area of the anionic polysaccharide substances to form cationic electric field potential energy, and then add mussel mucin, because it is a cationic positive charge, it repels the cationic electric field potential energy around the anionic polysaccharide substances. In this system, the two active substances are relatively independent and not easy to react, which solves the compatibility problem, expands the application field and improves the application efficacy.
[0066] In one embodiment, the composition specifically includes, by weight, 0.01-0.2 parts of mussel mucin, 0.05-1.0 parts of anionic polysaccharide, 0.3-3.0 parts of inorganic salt or citric acid, 3.0-20.0 parts of small molecule sugars, and 75.0-95.0 parts of water, wherein the number of sugar units of the small molecule sugars is less than 10. Adding small molecule sugars can further improve the long-term stability of the composition.
[0067] In one embodiment, the composition specifically includes, by mass percentage, 0.01-0.2% mussel mucin, 0.05-1.0% anionic polysaccharide, 0.3-3.0% inorganic salt or citric acid, 3.0-20.0% small molecule sugar, 1.0-3.0% preservative, 2.0-20.0% polyol and water to 100%, wherein the number of sugar units of the small molecule sugar is less than 10.
[0068] In one embodiment, the small molecule sugar substance is selected from at least one of mannitol, trehalose, sorbitol, xylitol, raffinose, sucrose, etc. Preferably, at least one of mannitol, trehalose, sorbitol, etc. is selected.
[0069] In one embodiment, the preservative may be a common preservative available on the market, such as methylparaben, propylparaben, phenoxyethanol, p-hydroxyacetophenone, 1,2-hexanediol, ethylhexylglycerin, sodium benzoate, and the like.
[0070] In one embodiment, the inorganic salt is selected from at least one of potassium salt, sodium salt, calcium salt, zinc salt, copper salt, magnesium salt, etc. Preferably, the inorganic salt is at least one of potassium chloride, sodium chloride, calcium chloride, zinc chloride, zinc sulfate, copper sulfate, and magnesium sulfate.
[0071] In one embodiment, the anionic polysaccharide material is at least one selected from hyaluronic acid or its salt, polyglutamic acid or its salt, colanic acid or its salt, β-glucan, etc. Preferably, it is one of hyaluronic acid or its salt, colanic acid or its salt, β-glucan, etc.
[0072] In one embodiment, the molecular weight of the hyaluronic acid or its salt is 0.1-2500 KDa, preferably 0.3-1800 KDa.
[0073] An embodiment of the present invention provides a method for preparing the composition containing mussel mucin and anionic polysaccharide as described above, which comprises the steps of mixing mussel mucin, anionic polysaccharide, inorganic salt or citric acid and water to obtain the composition.
[0074] The embodiment of the present invention can form a uniform and transparent composition by adding an appropriate amount of inorganic salt or citric acid to an aqueous solution containing mussel mucin and anionic polysaccharide. This compounding strategy allows the mussel mucin and anionic polysaccharide to be compatible and compounded, and has long-term stability, and can withstand aging experimental tests during the shelf life of the product, greatly improving the application scope and application efficacy of the above two substances.
[0075] In one embodiment, the step of mixing mussel mucin, anionic polysaccharide substance, inorganic salt or citric acid and water specifically comprises: adding inorganic salt or citric acid to the aqueous solution of anionic polysaccharide substance, and then adding mussel mucin.
[0076] In a specific embodiment, the step of mixing mussel mucin, anionic polysaccharide, inorganic salt or citric acid and water specifically comprises: adding inorganic salt to the aqueous solution of hyaluronic acid or its salt, and then adding mussel mucin.
[0077] Hyaluronic acid or colanic acid generally exists in the form of hyaluronate (such as sodium hyaluronate) or colanic acid (such as sodium colanate). In aqueous solution, sodium hyaluronate or sodium colanate is ionized into hyaluronic acid anion or colanic acid anion and sodium ion (Na + ), the positive charge of mussel mucin (NH 3+ ) is mainly due to the high content of lysine in its structure. A certain amount of inorganic salts, such as sodium chloride, potassium chloride, calcium chloride, zinc oxide, copper sulfate, magnesium sulfate, zinc sulfate and other water-soluble inorganic salts, are added to the aqueous solution of hyaluronic acid or its salt or the aqueous solution of colanic acid or its salt, and then mussel mucin is added to obtain a uniform and transparent solution. Different addition amounts can make the composition stable for a longer time under different conditions to meet the actual application requirements.
[0078] In one embodiment, the composition comprises, by mass percentage, 0.01-0.2% of mussel mucin, 0.05-1.0% of hyaluronic acid or its salt, 0.3-3.0% of inorganic salt or citric acid, 3.0-20.0% of small molecule sugar substances, 1.0-3.0% of preservatives, 2.0-20.0% of polyols, and water to 100%;
[0079] The preparation method of the composition comprises the steps of:
[0080] Mix small molecule sugar substances, preservatives, polyols and water, heat to 75-85°C to completely dissolve them, and keep warm for 20-30 minutes;
[0081] After cooling to 60-70°C, add hyaluronic acid or its salt and stir to completely dissolve;
[0082] After cooling to 50-60°C, slowly add inorganic salt or citric acid while stirring (speed 200-500rpm), stirring to completely dissolve;
[0083] The temperature was lowered to below 45°C and mussel mucin was slowly added while stirring (rotation speed 200-500 rpm) to obtain a clear and transparent composition.
[0084] It should be noted that, unless otherwise specified, % herein refers to mass percentage.
[0085] In a specific embodiment, the composition is formulated as shown in Table 1:
[0086] Table 1
[0087]
[0088] The preparation method of the above composition comprises the steps of:
[0089] 1. Add the raw materials in phase A into a beaker, heat to 75-85℃ to completely dissolve, and keep warm for 20-30 minutes;
[0090] 2. After cooling to 60-70℃, add the raw materials in phase B and stir to completely dissolve;
[0091] 3. After cooling to 50-60℃, slowly add the raw materials in phase C while stirring, stirring until they are completely dissolved;
[0092] 4. Cool down to below 45°C and slowly add the raw materials in phase D while stirring (speed 200-500 rpm) to obtain a clear and transparent composition.
[0093] An embodiment of the present invention provides a product, wherein the product comprises the composition containing both mussel mucin and anionic polysaccharide as described above.
[0094] In one embodiment, the product is a skin care product or a medical product, but is not limited thereto.
[0095] In one embodiment, the skin care product includes one of a facial mask, a medical dressing, a facial cream, a lotion, a freeze-dried powder, an essence, and a toner.
[0096] In other words, the above composition can be used to prepare skin care dosage forms such as facial masks, medical dressings, facial creams, lotions, freeze-dried powders, essences, toners, etc. to meet different application scenarios.
[0097] The present invention is further described in detail below through specific examples.
[0098] Example 1: Potassium Salt Group
[0099] The potassium salt group tested three potassium salts: dipotassium glycyrrhizinate, potassium azelayl diglycinate (azelaic acid derivative), potassium chloride, and three molecular weights of sodium hyaluronate: sodium hyaluronate with a molecular weight of 120-180KDa (referred to as HA1), sodium hyaluronate with a molecular weight of 10-50KDa (referred to as HA2), and sodium hyaluronate with a molecular weight of 3000-8000Da (referred to as HA3). The stability of the composition at different temperatures was tested. M505C (Manufacturer: Shenzhen Boyin Biotechnology Co., Ltd., mussel mucin content: 5000ppm).
[0100] Preliminary compatibility test: HA1 was selected for testing to test whether the two substances were compatible in the presence of inorganic salts.
[0101] The experimental formula is shown in Table 2:
[0102] Table 2
[0103]
[0104] The above results indicate that only the inorganic salt potassium chloride can promote the compatibility of mussel mucin and sodium hyaluronate.
[0105] Further stability testing of the compatible system with the addition of potassium chloride: Potassium chloride can promote the compatibility of mussel mucin and macromolecular sodium hyaluronate, but only the system that is compatible under different accelerated aging conditions for a long time is a system with application value.
[0106] The experimental formula is shown in Table 3 below:
[0107] Table 3
[0108]
[0109] The long-term (3 months) stability (aging conditions: 50°C, 38°C, 25°C, 4°C) results of the above samples are shown in Table 4:
[0110] Table 4
[0111]
[0112] The above test results show that with the synergy of inorganic salt potassium chloride and small molecule sugar substances, mussel mucin can be compatible with sodium hyaluronate of different molecular weights for a long time. The metal ions it contains not only promote the compatibility of the two active substances, but also achieve long-term stability.
[0113] Example 2: Sodium Salt Group
[0114] The sodium salt group tested three sodium salts: sodium chloride, disodium hydrogen phosphate, sodium dihydrogen phosphate, and three molecular weights of sodium hyaluronate: sodium hyaluronate with a molecular weight of 120-180KDa (referred to as HA1), sodium hyaluronate with a molecular weight of 10-50KDa (referred to as HA2), and sodium hyaluronate with a molecular weight of 3000-8000Da (referred to as HA3). The stability of the composition at different temperatures was tested. M505C (Manufacturer: Shenzhen Boyin Biotechnology Co., Ltd., mussel protein content: 5000ppm).
[0115] Preliminary compatibility test: HA1 was selected for testing to test whether the two substances were compatible in the presence of inorganic salts.
[0116] The experimental formula is shown in Table 5 below:
[0117] Table 5
[0118]
[0119] The above results show that only the inorganic salt sodium chloride can promote the compatibility of mussel mucin and high molecular weight sodium hyaluronate, while the other two common inorganic sodium salts do not have this function.
[0120] Preliminary compatibility test: HA2 was selected for testing to test whether the two substances were compatible in the presence of inorganic salts.
[0121] The experimental formula is shown in Table 6 below:
[0122] Table 6
[0123]
[0124] The above results show that only the inorganic salt sodium chloride can promote the compatibility of mussel mucin and medium molecular weight sodium hyaluronate, while the other two common inorganic sodium salts do not have this function.
[0125] Preliminary compatibility test: HA3 was selected for testing to test whether the two substances were compatible in the presence of inorganic salts.
[0126] The experimental formula is shown in Table 7 below:
[0127] Table 7
[0128]
[0129]
[0130] The above results show that only the inorganic salt sodium chloride can promote the compatibility of mussel mucin and low molecular weight sodium hyaluronate, while the other two common inorganic sodium salts do not have this function.
[0131] Further stability testing of the compatible system with sodium chloride addition (samples 12, 15, and 18): Sodium chloride can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights, but only the system that is compatible under different accelerated aging conditions for a long time is a system with application value.
[0132] The long-term (3 months) stability (aging conditions: 50°C, 38°C, 25°C, 4°C) results of the above samples are shown in Table 8:
[0133] Table 8
[0134]
[0135] The above test results show that with the synergy of inorganic salt sodium chloride, mussel mucin can be compatible with sodium hyaluronate of different molecular weights for a long time. The metal ions it contains not only promote the compatibility of the two active substances, but also achieve long-term stability.
[0136] Example 3: Calcium Salt Group
[0137] The calcium salt group tested one calcium salt: calcium chloride, and tested three molecular weights of sodium hyaluronate: sodium hyaluronate with a molecular weight of 120-180KDa (referred to as HA1), sodium hyaluronate with a molecular weight of 10-50KDa (referred to as HA2), and sodium hyaluronate with a molecular weight of 5000-8000Da (referred to as HA3), and tested the stability of the composition at different temperatures. M505C (Manufacturer: Shenzhen Boyin Biotechnology Co., Ltd., mussel protein content: 5000ppm).
[0138] Preliminary compatibility test: Test whether calcium chloride promotes the compatibility of mussel mucin with sodium hyaluronate (HA1-HA3).
[0139] The experimental formula is shown in Table 9 below:
[0140] Table 9
[0141]
[0142] The above results indicate that inorganic salt calcium chloride can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights.
[0143] Further stability testing of the compatible system with added calcium chloride (samples 19, 20, and 21): Calcium chloride can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights, but only the system that is compatible under different accelerated aging conditions for a long time is a system with application value.
[0144] The long-term (3 months) stability (aging conditions: 50°C, 38°C, 25°C, 4°C) results of the above samples are shown in Table 10:
[0145] Table 10
[0146]
[0147] The above test results show that with the synergy of inorganic salt calcium chloride, mussel mucin can be compatible with small and medium molecular weight sodium hyaluronate for a long time. The metal ions it contains not only promote the compatibility of the two active substances, but also achieve long-term stability.
[0148] Example 4: Copper Salt Group
[0149] The copper salt group tested two copper salts: copper sulfate and tripeptide-1 copper, and tested three molecular weights of sodium hyaluronate: sodium hyaluronate with a molecular weight of 120-180KDa (referred to as HA1), sodium hyaluronate with a molecular weight of 10-50KDa (referred to as HA2), and sodium hyaluronate with a molecular weight of 5000-8000Da (referred to as HA3). The stability of the composition at different temperatures was tested. M505C (Manufacturer: Shenzhen Boyin Biotechnology Co., Ltd., mussel protein content: 5000ppm).
[0150] Preliminary compatibility test: Test whether copper sulfate promotes the compatibility of mussel mucin with sodium hyaluronate (HA1-HA3).
[0151] The experimental formula is shown in Table 11 below:
[0152] Table 11
[0153]
[0154] The above results indicate that inorganic salt copper sulfate can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights.
[0155] Preliminary compatibility test: Test whether tripeptide-1 copper promotes the compatibility of mussel mucin and sodium hyaluronate (HA1-HA2).
[0156] The experimental formula is shown in Table 12 below:
[0157] Table 12
[0158]
[0159]
[0160] The above results indicate that tripeptide-1 copper cannot promote the compatibility of mussel mucin with large and medium molecular weight sodium hyaluronate. The possible reason is that copper ions are chelated by tripeptide-1 and cannot be released in the system, resulting in weak improvement ability.
[0161] Further stability testing of the compatible system with the addition of copper sulfate (samples 22, 23, 24, and 27): Copper sulfate can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights, but only the system that is compatible under different accelerated aging conditions for a long time is a system with application value.
[0162] The long-term (3 months) stability (aging conditions: 50°C, 38°C, 25°C, 4°C) results of the above samples are shown in Table 13:
[0163] Table 13
[0164]
[0165] The above test results show that, with the cooperation of inorganic salt copper sulfate or tripeptide-1 copper, mussel mucin can be compatible with small and medium molecular weight sodium hyaluronate for a long time, and has better compatibility with small molecule sodium hyaluronate. The metal ions contained not only promote the compatibility of the two active substances, but also achieve long-term stability.
[0166] Example 5: Zinc Salt Group
[0167] There are 4 candidate zinc salts in the zinc salt group: zinc sulfate, zinc chloride, PCA zinc, and zinc gluconate. Based on the experimental results of the compatibility of tripeptide-1 copper with two active ingredients, if the metal ions are in a chelated state, it is possible that the metal ions will limit the compatibility of the system. Therefore, only the effects of zinc sulfate and zinc chloride (auxiliary trace acid) were tested. Three molecular weights of sodium hyaluronate were tested: sodium hyaluronate with a molecular weight of 120-180KDa (denoted as HA1), sodium hyaluronate with a molecular weight of 10-50KDa (denoted as HA2), and sodium hyaluronate with a molecular weight of 5000-8000Da (denoted as HA3). The stability of the composition at different temperatures was tested. Trade name of mussel mucin: M505C (Manufacturer: Shenzhen Boyin Biotechnology Co., Ltd., mussel protein content: 5000ppm).
[0168] Preliminary compatibility test: Test whether zinc sulfate promotes the compatibility of mussel mucin with sodium hyaluronate (HA1-HA3).
[0169] The experimental formula is shown in Table 14 below:
[0170] Table 14
[0171]
[0172] The above results indicate that inorganic zinc sulfate can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights.
[0173] Preliminary compatibility test: Test whether zinc chloride promotes the compatibility of mussel mucin with sodium hyaluronate (HA1-HA3).
[0174] The experimental formula is shown in Table 15 below:
[0175] Table 15
[0176]
[0177] The above results indicate that inorganic salt zinc chloride can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights.
[0178] Further stability testing of the compatible system with the addition of zinc sulfate and zinc chloride (samples 28-33): The two zinc salts can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights, but only the system that is compatible under different accelerated aging conditions for a long time is a system with application value.
[0179] The long-term (3 months) stability (aging conditions: 50°C, 38°C, 25°C, 4°C) results of the above samples are shown in Table 16:
[0180] Table 16
[0181]
[0182]
[0183] The above test results show that, with the cooperation of inorganic salt zinc chloride, mussel mucin can be compatible with sodium hyaluronate of different molecular weights for a long time; compared with zinc sulfate, zinc chloride has better long-term stability compatibility. The metal ions contained not only promote the compatibility of the two active substances, but also achieve long-term stability.
[0184] Example 6: Fruit acid group
[0185] The fruit acid group included five candidate acids: citric acid, malic acid, tartaric acid, glycolic acid, and lactic acid. Three molecular weights of sodium hyaluronate were tested: sodium hyaluronate with a molecular weight of 120-180 KDa (referred to as HA1), sodium hyaluronate with a molecular weight of 10-50 KDa (referred to as HA2), and sodium hyaluronate with a molecular weight of 5000-8000 Da (referred to as HA3). The stability of the composition at different temperatures was tested. M505C (Manufacturer: Shenzhen Boyin Biotechnology Co., Ltd., mussel protein content: 5000ppm).
[0186] Preliminary compatibility test: Test whether citric acid promotes the compatibility of mussel mucin and sodium hyaluronate (HA1-HA3).
[0187] The experimental formula is shown in Table 17 below:
[0188] Table 17
[0189]
[0190] The above results indicate that citric acid can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights.
[0191] Preliminary compatibility test: Test whether malic acid promotes the compatibility of mussel mucin and sodium hyaluronate (HA1-HA3).
[0192] The experimental formula is shown in Table 18 below:
[0193] Table 18
[0194]
[0195] The above results indicate that malic acid cannot promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights.
[0196] Preliminary compatibility test: Test whether glycolic acid promotes the compatibility of mussel mucin and sodium hyaluronate (HA1-HA3).
[0197] The experimental formula is shown in Table 19 below:
[0198] Table 19
[0199]
[0200] The above results indicate that glycolic acid cannot promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights.
[0201] Preliminary compatibility test: Test whether lactic acid promotes the compatibility of mussel mucin and sodium hyaluronate (HA1-HA3).
[0202] The experimental formula is shown in Table 20 below:
[0203] Table 20
[0204]
[0205]
[0206] The above results indicate that lactic acid cannot promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights.
[0207] Further stability testing of the compatible system with added citric acid (samples 34-36): Citric acid can promote the compatibility of mussel mucin with sodium hyaluronate of different molecular weights, but only the system that is compatible under different accelerated aging conditions for a long time is a system with application value.
[0208] The above long-term (3 months) stability (aging conditions: 50°C, 38°C, 25°C, 4°C) results are shown in Table 21:
[0209] Table 21
[0210]
[0211] The above test results show that with the synergy of citric acid, mussel mucin can be compatible with sodium hyaluronate of different molecular weights for a long time.
[0212] Example 7: Comparison of repair effects on sensitive skin (potassium and sodium groups)
[0213] The compositions in Examples 1 and 2 (i.e., samples 4, 5, and 12) and a placebo were selected to conduct comparative tests on moisturizing, reducing transepidermal water loss, and removing redness on people with sensitive skin. The specific test formulas are shown in Table 22:
[0214] Table 22
[0215]
[0216]
[0217] Preparation method:
[0218] Step 1: Heat phase A and phase B to 80°C respectively, stir (300 rpm) to dissolve evenly, and keep warm for 25 minutes; add phase B to phase A, stir (400 rpm) for emulsification, homogenize (2500 rpm) for 2 minutes, vacuum to defoam, and then cool down;
[0219] Step 2: Cool down to about 60°C, add phase C, and stir (250 rpm) evenly;
[0220] Step 3: Cool down to below 45°C, add phase D, and stir (250 rpm) evenly;
[0221] Step 4: Conduct relevant physical and chemical tests and repackage after passing the tests.
[0222] Description: Placebo component A + B two products (A dosage form contains the same amount of mussel mucin, B dosage form contains the same amount of sodium hyaluronate)
[0223] The experimental test information is as follows:
[0224] Test purpose: Evaluation of cosmetics efficacy on human body
[0225] Test items: Repair, suitable for sensitive skin
[0226] Reference standards: QB / T 4256-2011 Guidelines for the evaluation of moisturizing efficacy of cosmetics; T / GDCA
[0227] 009-2022 Human evaluation method for repairing efficacy; T / CNMIA0015-2020 Clinical evaluation standard for soothing efficacy skin care products
[0228] Test population: Gender is not limited, age is 18-60 years old, lactic acid tingling screening is for sensitive skin people
[0229] Test area: face
[0230] Test environment: temperature 21℃±1℃; humidity 50%±10%RH
[0231] Test instruments: Stratum corneum moisture content tester; Transepidermal water loss tester; C-cube imager
[0232] Follow-up time: 0 days, 3 days, 7 days, 14 days, 28 days after using the product
[0233] Bad record: None
[0234] Screening test for sensitive skin: This test screened 15 people with sensitive skin to participate in the sample efficacy evaluation through the following scheme
[0235] Sample usage: After cleansing in the morning and evening, apply appropriate amount of product evenly on the face and gently massage until absorbed.
[0236] Lactic acid sting test:
[0237] Take 50μl of 10% lactic acid solution and drop it on a 1*1cm non-woven fabric. Apply the non-woven fabric to the nasolabial groove on either side of the subject, and use distilled water as a control on the other side. The tester asked the subject about the tingling sensation at 0.5, 2.5, and 5 minutes, and scored according to the "4-point method" in the table below. Those with a cumulative tingling sensation of ≥3 points on the lactic acid side relative to the distilled water side are considered to have lactic acid tingling and can be judged as sensitive skin. The lactic acid tingling score is shown in Table 23 below:
[0238] Table 23
[0239]
[0240] Moisturizing effect comparison, characterized by the increase in water content in the stratum corneum of the skin, the results are as follows Fig. 20As shown, the significant annotation method: "ns" indicates no statistical difference, p≥0.05; p<0.05 indicates a significant difference; "*" indicates 0.01≤p<0.05; "**" indicates 0.001≤p<0.01; "***" p<0.001. Compared with D0, sample groups 4, 5, 12 and the placebo group significantly increased the water content of the skin on days 3, 7, 14 and 28, indicating that the samples have a repairing effect on the skin. It shows that products containing mussel mucin and sodium hyaluronate can increase the moisture content of sensitive skin. Compared with the placebo group, the increase in the moisture content of sensitive skin in sample groups 4, 5, and 12 at the same time point was greater than that in the placebo group, indicating that the addition of relevant metal components to the composition is not only beneficial for the two classic ingredients to be compounded with each other, but also can synergistically enhance the moisturizing effect, which is helpful for the care of sensitive skin.
[0241] The repair effect is compared by reducing the transepidermal water loss rate. The results are as follows Fig.21 , where the significance marking method is: "ns" means no statistical difference, p≥0.05; p<0.05, means there is a significant difference; "*" means 0.01≤p<0.05; "**" means 0.001≤p<0.01; "***" means p<0.001. Compared with D0 day, sample groups 4, 5, 12 and the placebo group all significantly reduced the transepidermal water loss rate of the skin on day 28, indicating that the samples have a repairing effect on the skin. It shows that products containing mussel mucin and sodium hyaluronate can reduce the transepidermal water loss rate of sensitive skin. Compared with the placebo group, the reduction rate of transepidermal water loss in sample groups 4, 5, and 12 was greater than that in the placebo group, indicating that the addition of relevant metal components in the composition is not only beneficial for the two classic ingredients to be compounded with each other, but also can synergistically enhance the repair effect on sensitive skin and enhance the barrier function of sensitive skin.
[0242] The redness-removing effect is compared by the decrease of the a value of the skin red area and the erythema index E value. The results are as follows Figure 22-23 , where the significance annotation method is: "ns" means no statistical difference, p≥0.05; p<0.05, means significant difference; "*" means 0.01≤p<0.05; "**" means 0.001≤p<0.01; "***" p<0.001. Compared with D0 day, sample 4, 5, 12 groups and placebo group significantly reduced the skin red zone a value and erythema index E value on 28 days, indicating that the samples have a redness-removing effect on the skin. It shows that products containing mussel mucin and sodium hyaluronate can relieve the redness of sensitive skin. Compared with the placebo group, the proportion of the decrease in skin a value and E value in sample 4, 5, and 12 groups was greater than that in the placebo group, indicating that the addition of relevant metal components in the composition is not only beneficial for the two classic ingredients to be compounded with each other, but also can synergistically enhance the repair effect on sensitive skin and enhance the barrier function of sensitive skin.
[0243] Four groups of samples, namely, samples 9, 23, 27 and placebo, were selected for efficacy comparison test. The specific test formula was the same as that in Table 22, with the only difference being that the samples were samples 9, 23 and 27. The soothing efficacy comparison was represented by pictures, and the results are shown below. Fig.24 As shown. Compared with D0, samples 9, 23, 27 and the placebo group all significantly reduced skin redness on day 28, indicating that the samples have a soothing effect on the skin. This shows that products containing mussel mucin and sodium hyaluronate can relieve the redness of sensitive skin. Compared with the placebo group, samples 9, 23, and 27 improved skin redness better, indicating that the addition of relevant metal components to the composition is not only beneficial for the two classic ingredients to be compounded with each other, but also can synergistically enhance the repair effect on sensitive skin and enhance the barrier function of sensitive skin.
[0244] The experimental test information is as follows:
[0245] Test purpose: Evaluation of cosmetics efficacy on human body
[0246] Test items: Suitable for firming and sensitive skin
[0247] Reference standard: T / ZHCA006-2019 Test method for anti-wrinkle efficacy of cosmetics
[0248] Test population: Gender is not limited, age is 30-65 years old, lactic acid tingling screening is for sensitive skin people
[0249] Test area: face
[0250] Test environment: temperature 21℃±1℃; humidity 50%±10%RH
[0251] Test equipment: Antera 3D
[0252] Follow-up time: 0 days, 3 days, 7 days, 14 days, 28 days after using the product
[0253] Bad record: None
[0254] Screening test for sensitive skin: This test screened 15 people with sensitive skin to participate in the sample efficacy evaluation through the following scheme;
[0255] Sample usage: After cleansing in the morning and evening, apply appropriate amount of product evenly on the face and gently massage until absorbed.
[0256] Lactic acid sting test:
[0257] Take 50μl of 10% lactic acid solution and drop it on a 1*1cm non-woven fabric. Apply the non-woven fabric to the nasolabial groove on either side of the subject, and use distilled water as a control on the other side. The tester asked the subject about the tingling sensation at 0.5 / 2.5 / 5min, and scored according to the "4-point method" in the table below. Those with a cumulative tingling sensation of ≥3 points on the lactic acid side relative to the distilled water side are considered to have lactic acid tingling and can be judged as sensitive skin. The lactic acid tingling score is shown in Table 24 below:
[0258] Table 24
[0259]
[0260]
[0261] Comparison of firming effects, comparing the number and length of under-eye wrinkles, the results are as follows Figure 25-26 ; Among them, the significant annotation method: "ns" means no statistical difference, p ≥ 0.05; p < 0.05, means there is a significant difference; "*" means 0.01 ≤ p < 0.05; "**" means 0.001 ≤ p < 0.01; "***" means p < 0.001. Compared with D0, sample 27, 23, 9 and placebo group significantly reduced the number of under-eye wrinkles on days 7 and 28. Compared with the placebo group, sample 27 showed better improvement effect, and the other two groups of samples had better results than the placebo group at different time points; compared with D0, sample 27, 23, 9 groups significantly reduced the length of under-eye wrinkles on days 7, 14, and 28, showing better improvement effect compared with the placebo group. The above results show that the samples containing active ingredients have a firming effect on the skin. The addition of relevant metal components in the composition is not only beneficial for the two classic ingredients to be compounded with each other, but also can synergistically enhance the moisturizing effect, which is helpful for the firming care of sensitive skin.
[0262] Comparison of firming effects, comparing and evaluating the effects by the number and length of eye wrinkles, the results are as follows Figure 27-28 As shown; where the significance annotation method: "ns" means no statistical difference, p≥0.05; p<0.05, means there is a significant difference; "*" means 0.01≤p<0.05; "**" means 0.001≤p<0.01; "***" means p<0.001. Compared with D0, sample 27 significantly reduced the number of eye tail wrinkles on days 14 and 28, and the results were better than the placebo group. Compared with D0, samples 27, 23, and 9 significantly reduced the length of eye tail wrinkles on days 3, 7, 14, and 28, which was better than the placebo group, indicating that the samples have a firming effect on the skin. It shows that the addition of relevant metal components in the composition is not only beneficial for the two classic ingredients to be compounded with each other, but also can synergistically enhance the moisturizing effect, which is helpful for the firming care of sensitive skin.
[0263] Comparison of firming effects, through the actual case pictures of under-eye and eye-tail wrinkles, the results are as follows Fig.29 As shown. Compared with D0, samples 27, 23, 9 and the placebo group significantly increased the water content of the skin on days 3, 7, 14 and 28, indicating that the samples have a repairing effect on the skin. This shows that products containing mussel mucin and sodium hyaluronate can increase the moisture content of sensitive skin. Compared with the placebo group, the increase in the moisture content of sensitive skin in sample groups 27, 23 and 9 was greater than that in the placebo group at the same time point, indicating that the addition of relevant metal components to the composition is not only beneficial for the two classic ingredients to be compounded with each other, but also can synergistically enhance the moisturizing effect, which is helpful for the care of sensitive skin.
[0264] Example Sample 19: Efficacy for eczema / wound repair
[0265] Apply the product to the affected area and it will heal in 3-5 days. Figure 30-31 It can be seen.
[0266] Embodiment 8:
[0267] Different anionic polysaccharides were selected for testing to test whether mussel mucin is compatible with different anionic polysaccharides in the presence of inorganic salts. The experimental formula is shown in Table 25 below.
[0268] Table 25
[0269]
[0270]
[0271] From Table 25 and Fig.32 The results show that some anionic polysaccharides can be compatible with mussel mucin, while the improvement effect of thickening type anionic polysaccharides (xanthan gum, sclerotium gum, etc.) is poor. The combination of mussel mucin and some anionic polysaccharides can improve their respective application range and efficacy.
[0272] In summary, the present invention provides a composition containing mussel mucin and anionic polysaccharide substances at the same time, and a preparation method and product thereof. The present invention forms a uniform and transparent composition by adding an inorganic salt or citric acid to an aqueous solution containing mussel mucin and anionic polysaccharide substances. This strategy enables the two substances, mussel mucin and anionic polysaccharide substances, to be compatible and compounded, and has long-term stability, and can withstand aging experimental inspection and testing during the shelf life of the product, greatly improving the application scope and application efficacy of the above two substances.
[0273] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A composition containing mussel mucin and anionic polysaccharide substances, characterized in that: The composition comprises, by mass, 0.01-0.2 parts of mussel mucin, 0.05-1.0 parts of anionic polysaccharide, 0.3-3.0 parts of inorganic salt or citric acid and 75.0-95.0 parts of water.
2. The composition containing mussel mucin and anionic polysaccharide substances according to claim 1, characterized in that: In parts by mass, the composition specifically includes 0.01-0.2 parts of mussel mucin, 0.05-1.0 parts of anionic polysaccharide, 0.3-3.0 parts of inorganic salt or citric acid, 3.0-20.0 parts of small molecule sugar substances and 75.0-95.0 parts of water, wherein the number of sugar units in the small molecule sugar substances is less than 10.
3. The composition containing mussel mucin and anionic polysaccharide substances according to claim 1, characterized in that: Calculated by mass percentage, the composition specifically includes 0.01-0.2% of mussel mucin, 0.05-1.0% of anionic polysaccharide, 0.3-3.0% of inorganic salt or citric acid, 3.0-20.0% of small molecule sugar, 1.0-3.0% of preservative, 2.0-20.0% of polyol and water to 100%, wherein the number of sugar units of the small molecule sugar is less than 10.
4. The composition containing mussel mucin and anionic polysaccharide substances according to claim 2 or 3, characterized in that: The small molecule sugar substance is selected from at least one of mannitol, trehalose, sorbitol, xylitol, raffinose and sucrose.
5. The composition containing mussel mucin and anionic polysaccharide substances according to claim 1, characterized in that: The inorganic salt is selected from at least one of potassium salt, sodium salt, calcium salt, zinc salt, copper salt and magnesium salt.
6. The composition containing mussel mucin and anionic polysaccharide substances according to claim 5, characterized in that: The inorganic salt is selected from at least one of potassium chloride, sodium chloride, calcium chloride, zinc chloride, zinc sulfate, copper sulfate and magnesium sulfate.
7. The composition containing mussel mucin and anionic polysaccharide substances according to claim 1, characterized in that: The anionic polysaccharide substance is selected from at least one of hyaluronic acid or its salt, polyglutamic acid or its salt, colanic acid or its salt, and β-glucan; The molecular weight of the hyaluronic acid or its salt is 0.1-2500 KDa.
8. A method for preparing the composition containing mussel mucin and anionic polysaccharide substances according to claim 1, characterized in that: The method comprises the steps of: mixing mussel mucin, anionic polysaccharide material, inorganic salt or citric acid and water to obtain the composition.
9. The method for preparing the composition containing mussel mucin and anionic polysaccharide substances according to claim 8, characterized in that: The step of mixing mussel mucin, anionic polysaccharide substance, inorganic salt or citric acid and water specifically comprises: adding inorganic salt or citric acid to the aqueous solution of anionic polysaccharide substance, and then adding mussel mucin.
10. A product, characterized in that The product comprises the composition containing mussel mucin and anionic polysaccharide substances as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Composition for improving skin barrier
CN109925501A
Composition for increasing water content of stratum corneum
CN110731911A
Sticky antibacterial repair material and preparation method and application thereof
CN110917120A
Hydrophilic injection type skin filling composition, preparation method and application thereof
CN114028610A
Moisturizing and repairing essence lotion and preparation method thereof
CN115400034A